Noun Phrase in the Lyrics of Billie Eilish: Visualizing and Tree Diagrams Analysis - Dewi Anggi Lestari; Dadan Rusmana; Irman Nurhapitudin (Journal of English Language and Education, 2026)
This study examines noun phrases (NPs) in selected lyrics by Billie Eilish, namely Lovely, Ilomilo, and What Was I Made For? Previous studies have mainly focused on discourse analysis, thematic interpretation, and sentence-level syntax, while limited attention has been given to noun phrases, particularly their internal structure and role in meaning construction. This gap indicates the need for a focused syntactic analysis of noun phrases in lyrical discourse. The study aims to identify types of noun phrases, analyze their internal structures, and explain their contribution to emotional meaning. A descriptive qualitative method was applied, with data collected through documentation of song lyrics. The analysis covers 23 noun phrases, consisting of 8 from Lovely, 4 from What Was I Made For? and 11 from Ilomilo. The data were analyzed using identification, classification of structural patterns, and phrase structure rules based on generative grammar. Findings show that noun phrases appear in various forms such as determiner + noun (e.g., a way), possessive constructions (e.g., my fear), and complex structures with post-modifiers (e.g., a place to hide, the friends I’ve had to bury). These noun phrases function not only as grammatical units but also as carriers of emotional meaning, expressing uncertainty, loss, identity, and longing. The study concludes that noun phrases bridge syntactic structure and emotional expression in song lyrics.